Model tests of prefabricated horizontal drains with vacuum preloading on clay slurry for land reclamation - Teo, Brenda, Jia Wen (2016)
With the upcoming plans for the development of the country, Singapore needs to increase her territory to keep up with the economy. Singapore reclaims land to increase her land space. However, Singapore has a drastic lack of land fill materials because her resources have been depleted. Singapore has been searching for materials and exports from other countries to fill up the shortage of materials. Recently, import bans were imposed on her and hence, she has to explore other materials to use for land reclamation other than using the typical materials, sand and gravels. Cohesive soils such as marine clay have been studied to replace the usual materials because cohesive soils have different properties as non-cohesive soil. Cohesive soils display large settlements and have low bearing capacities. Soil improvement methods are needed to strengthen cohesive soils and to increase the rate of consolidation. Hence, this project aims to improve the properties of cohesive soils by proposing the use of vacuum preloading and prefabricated horizontal drains.